Three-Phase Phase-Shifting Transformer with Regulation in Neutral Point - Kalinin L.P.; Zaitsev D.A.; Tirshu M.; Golub I.V.; Moraru L. (Problems of the Regional Energetics)
The paper aimed to research mode characteristics of phase shift installation based on one three-phase transformer having three windings. Usually, such installations are two cores: exciting transformer and regulation transformer. In paper the installation functional scheme description, as well main relations which determine currents and voltages character in scheme elements during regulation process are given. It is shown, that installation is able to provide phase shift angle regulation up to . The installation scheme is designed to place the control module in the neutral connection point of regulation windings. Such solution allowing essential reduction of installation rated capacity compare to traditional one and excluding necessity of special isolation of shell. Proposed solution ensure in such mode compact construction and commodity for transportation, mounting and service.